Advances in cyclin-dependent kinase inhibitors for the treatment of melanoma. (11th February 2021) - Julve, Maximilian; Clark, James J.; Lythgoe, Mark P.
ABSTRACT: Introduction: Despite the recent advances in the treatment of malignant melanoma with immunotherapy and BRAF/MEK targeted agents, advanced disease still beholds a poor prognosis for a significant proportion of patients. Cyclin-dependent kinase (CDK) inhibitors have been investigated as novel melanoma therapeutics throughout a range of phase 1 and 2 trials, as single agents and in combination with established treatments. Areas covered: This article summarizes the rationale for, and development of CDK inhibitors in melanoma, with their evolution from pan-CDK inhibitors to highly specific agents, throughout clinical trials and finally their potential future use. Expert opinion: Whilst CDK inhibitors have been practice changing in breast cancer management, their efficacy is yet to be proven in melanoma. Combination with BRAF/MEK inhibitors has been hindered by dose-limiting toxicities, but their role may yet to be found within the spectrum of biomarker-derived personalized melanoma management. The effect that CDK inhibitors can have as an adjunct to immunotherapy also remains to be seen.